Impact of Incorporation of Active Nanoporous Components or Their Precursors in a CuAlO/CuAl Ceramometal Skeleton on the Properties in the Low-Temperature Water-Gas Shift Reaction - Tikhov, Serguei F. (ACS Omega, 2020)
[Image: see text] Enhanced activity in low-temperature water-gas shift (LT-WGS) reaction of some ceramometal catalysts compared to conventional Cu–Zn–Al oxide catalyst was demonstrated. Porous ceramometals were synthesized from powdered CuAl alloys prepared by mechanical alloying with the addition of either CuAl(exp) powders produced by current spark explosion of Cu+Al wires or CuZnAl oxide obtained by coprecipitation. Their structural, microstructural, and textural characteristics were examined by means of X-ray diffraction, scanning electron microscopy with energy-dispersive X-ray spectrometry, NMR, and adsorption methods, and catalytic properties were studied in the LT-WGS reaction. CuAlO/CuAl ceramometals were found to have mostly the egg-shell microstructure with the metallic cores (Al(x)Cu(1–x), Al(2)Cu, and Al(4)Cu(9)) and the oxide shell containing copper oxides and/or mixed oxides of copper and aluminum and, at same time, CuAlO/CuAl ceramometal with incorporated additives was found to create a more complicated microstructure. A large amount of X-ray amorphous oxides of copper and aluminum is typical for all composites. CuAl ceramometal was shown to be more active than the CuZnAl oxide catalyst in spite of a much lower specific surface area. The CuAl+CuZnAl catalyst consisting of prismatic granules showed a higher activity in comparison with CuZnAl oxide consisting of cylindrical granules. The activity of the composite granulated catalyst referred to its unit weight was more than 6-fold higher as compared to the oxide catalyst, while the activity per the surface area was found to be more than an order of magnitude higher due to much higher specific activity of small fraction and additively much lower diffusion limitation of granules.